2016
DOI: 10.1039/c6tb02149b
|View full text |Cite
|
Sign up to set email alerts
|

Influence of titanium dioxide nanorods with different surface chemistry on the differentiation of rat bone marrow mesenchymal stem cells

Abstract: In this study, four kinds of TiO2 nanorods (TiO2 NRs), with similar aspect ratios but different surface functional groups, i.e. amines (–NH2), carboxyl groups (–COOH) and poly(ethylene glycol) (–PEG), were used to study their interaction with rat bone marrow stem cells (MSCs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 80 publications
0
26
0
Order By: Relevance
“…Type I collagen is a major component of bone matrix proteins, which was secreted at the early phase of osteoid matrix deposition and modulated cell differentiation, and the expression of collagen I was a nonspecific marker of new bone formation. 30 In this study, the results of type I collagen staining and quantitative analysis of type I collagen expression revealed that the expression of type I collagen for 30 MGPC was significantly higher than 15 MGPC, and 15 MGPC was higher than GPC scaffold, indicating that 30 MGPC promoted remarkable new bone formation compared with 15 MGPC and GPC scaffolds. Therefore, the immunohistochemical analysis of type I collagen further offered the direct evidence of the stimulatory effect on cells osteogenic differentiation and osteoid matrix deposition in vivo with the help of 30 MGPC scaffold.…”
Section: Discussionmentioning
confidence: 59%
“…Type I collagen is a major component of bone matrix proteins, which was secreted at the early phase of osteoid matrix deposition and modulated cell differentiation, and the expression of collagen I was a nonspecific marker of new bone formation. 30 In this study, the results of type I collagen staining and quantitative analysis of type I collagen expression revealed that the expression of type I collagen for 30 MGPC was significantly higher than 15 MGPC, and 15 MGPC was higher than GPC scaffold, indicating that 30 MGPC promoted remarkable new bone formation compared with 15 MGPC and GPC scaffolds. Therefore, the immunohistochemical analysis of type I collagen further offered the direct evidence of the stimulatory effect on cells osteogenic differentiation and osteoid matrix deposition in vivo with the help of 30 MGPC scaffold.…”
Section: Discussionmentioning
confidence: 59%
“…2C, almost no green uorescence appeared in the three control groups, indicating there was no adequate ROS generation in cells to oxidize no-uorescent DCFH-DA to uorescent dichlorouorescein (DCF). [31][32][33][34][35][36][37][38] In contrast, bright green uorescence emerged in Co-NRs group with light irradiation, suggesting the generation of ROS.…”
Section: Resultsmentioning
confidence: 92%
“…Iron oxide NPs decorated with neutrally charged glucose ligands elicited higher ROS levels in CT26 colorectal cancer cells than did their citrate-decorated counterparts with a negative surface charge (Wydra et al, 2015). In rat bone marrow mesenchymal stem cells, pristine and NH 2 -TiO 2 NRs (60 × 8 nm) induced ROS production, while COOH-TiO 2 NRs had no significant impact (Shrestha et al, 2016). Therefore, it seems that the positively charged and neutral oxide NPs described above are more likely to induce ROS than are their negatively charged counterparts.…”
Section: Surface Chargementioning
confidence: 94%
“…Few TiO 2 NPs decorated with PEG-like polymers were internalized into A549 and H1299 cells (Tedja et al, 2012). In another study, PEG decorated TiO 2 NRs (50-65 nm in length and 8 nm in width) were internalized to a lesser extent into rat bone marrow mesenchymal stem cells compared to the internalized levels of NRs with NH 2 or COOH decorations (Shrestha et al, 2016). PEG decoration on ZnO NPs (39 nm) reduced the internalization into THP-1 and differentiated THP-1 cells compared to levels of NPs with APTES decoration that were internalized (Luo et al, 2014).…”
Section: Hydrophobicitymentioning
confidence: 98%
See 1 more Smart Citation